Tribological Behaviour of Neem Oil with and without Graphene Nanoplatelets Using Four-Ball Tester. (25th January 2020) - Suresha, B.; Hemanth, G.; Rakesh, Apurva; Adarsh, K. M.
Abstract : The present work was aimed to study the friction and wear behaviour of graphene nanoplatelets (GNPs) under extreme pressure conditions as an anti-weld additive for neem oil. The effect of neem oil, blended with various loading of GNPs on the friction and wear characteristics has been investigated. From the experimental results, it was found that 1 wt.% of GNPs in neem oil showed the least coefficient of friction and smoother wear scar diameter. The extreme pressure test was performed on neem oil with and without GNPs as per ASTM standards. The extreme pressure test results indicated the improvement in seizure load of neem oil by 27.8% at 0.5 wt.% of GNPs as compared to pure neem oil. Optical microscopy of worn steel ball surface revealed the pit formation and the formation of wedge cutting edge in GNPs modified neem oil.